2021
DOI: 10.1002/ptr.7296
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of wild lowbush blueberry (Vaccinium angustifolium) on global cerebral ischemia/reperfusion injury in rats: Downregulation of iNOS/TNF‐α and upregulation of miR‐146a/miR‐21 expression

Abstract: This study aims to investigate the neuroprotective effect of wild lowbush blueberry on CIRI in rats. Accordingly, CIRI and reperfusion were induced in rats for 60 min and 24 h, respectively. Then, the mechanisms of the neuroprotective effects of BBE were investigated in the injury through evaluating miR-146a, miR-21, and their targets in a CIRI rat model. After that, the BBE (30, 60, and 120 mg/kg b.wt) was intraperitoneally injected for 14 days, then CIRI was induced by BCCAO for 60 min for ischemic stroke an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This test requires relatively short-term, synaptic/initial memory consolidation, which is well described as occurring in the hippocampal region – with recent evidence specifically identifying a key role of the amygdala [ 52 ]. Interestingly, numerous recent animal studies have shown adaptations in neuroinflammation and neuroplasticity of the hippocampal region following blueberry extract or blueberry (poly)phenol interventions [ 49 , [53] , [54] , [55] , [56] ], which suggests this may be a priority area to focus on in future human studies.…”
Section: Discussionmentioning
confidence: 99%
“…This test requires relatively short-term, synaptic/initial memory consolidation, which is well described as occurring in the hippocampal region – with recent evidence specifically identifying a key role of the amygdala [ 52 ]. Interestingly, numerous recent animal studies have shown adaptations in neuroinflammation and neuroplasticity of the hippocampal region following blueberry extract or blueberry (poly)phenol interventions [ 49 , [53] , [54] , [55] , [56] ], which suggests this may be a priority area to focus on in future human studies.…”
Section: Discussionmentioning
confidence: 99%
“…Contained in blueberry, flavonoids, and polyphenols have been reported to have therapeutic effects on neurological disease [ 78 , 79 ]. A benefit of blueberry supplements in cardiovascular disease was demonstrated using randomized controlled trials and discovered the regulating of inflammatory factors [ 51 ]. The prevention of stroke promoted by polyphenols relies mainly on their effect on ischemic stroke systems including neuroprotective roles in many cellular mechanisms [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a wild lowbush blueberry had neuroprotective effects on global cerebral ischemia/reperfusion injured rats through downregulation of iNOS/TNF-α and upregulation of miR-146a/miR21 expression [ 51 ]. Similarly, when neuronal cells were treated with those genes under OGD conditions, a significant increase in expression was observed in B-EVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-146a is central to neuroinflammation by modulating the NF-κB signaling pathway activity. It substantially impacts the homeostasis of immune and brain cells, neuronal identities, identity acquisition, and immune response regulation in the nervous system (18). Abnormal expression of miR-146a can cause the uncontrolled generation of neurotoxic inflammatory factors, such as IL-1, TNF-α, nitric oxide (NO), and hydrogen peroxide (H 2 O 2 ), eventually leading to neuronal death and neurodegeneration (19,20).…”
Section: Figurementioning
confidence: 99%